Experimental and numerical investigations on extinction strain rates in non-premixed counterflow methane and propane flames in an oxygen reduced environment. (15th August 2021) - Eckart, Sven; Yu, Chunkan; Maas, Ulrich; Krause, Hartmut
Graphical abstract: Highlights: This work experimentally and numerically analyzed the extinction strain rate for methane, ethene and propane flames as well as the impact of the oxygen and fuel mass ratio. A non-linear influence was found with decreasing fuel content and decreasing oxygen content in either case to decrease of the extinction strain rate. The effects of radiative heat loss, molecular transport model and chemical reactions on the ESRs are studied numerically. Radiative heat loss plays a minor effect on the ESRs, the molecular transport model is more significant. Via radical detection it was possible to investigate the width, intensity and position of the flame front. a new laser-based approach for flame extinction detection was described in this study. Abstract: The aim of this work is to contribute to the better understanding of the oxidation process of light hydrocarbons, low calorific value gas and components of natural gas in the presence of inert gases and the influence of oxygen reduction in exhaust gas recirculation situations. The extinction behavior of laminar counterflow diffusion flames of methane (CH4 ), ethene (C2 H4 ) and propane (C3 H8 ) under nitrogen diluted condition has been investigated experimentally and numerically. In the experimental set-up, a counterflow burner was employed to investigate the extinction behavior under atmospheric conditions (1 bar and 298 K). The present study highlights the non-linear influence on the decrease in the extinction strain rate (ESR) that were found with decreasing fuel content and decreasing oxygen content. The oxygen content on the oxide side was stepwise diluted with nitrogen in order to distinctly show the possible oxygen-depleted influence in the recirculation areas. Additionally, it has been shown that the distance between the nozzles has an impact on the ESR but not on the general rising trend with the increasing fuel content in the non-premixed flames. Moreover, to clarify the influence, the flame zones were visualized using a system of high-speed OH* chemiluminescence camera. It was possible to investigate the width, intensity and position of the flame front from the radical detection. This provided a comprehensive data base for the subsequent numerical validation. In order to complement the experimental investigations, extensive uncertainty analyses were conducted and a new laser-based approach for the detection of flame extinction were demonstrated for the low-visible flames. Besides the experimental study, ESRs of CH4 and C3 H8 combustion obtained from the experimental measurements were compared with those predicted by the numerical simulations. The San Diego-2014 reaction mechanism was used to represent the detailed chemical reaction, in which the predicted ESRs agree well with the experimental data was shown. Additionally, the effects of radiative heat loss, molecular transport model and chemical reactions on the ESRs were studied numerically. The present results suggest that the radiative heat loss plays a minor role on the ESRs, the molecular transport model is more significant and the ESRs are quite sensitive to several key reactions.